A Study of Object Transparency Via Charge-Coupled Device Mathematical Modelling Assessment - Syarfa Najihah Raisin; Fatinah Mohd Rahalim; Bushra Naeem; Farah Aina Jamal Mohamad; Ahmad Syahmi Mohd Zain; Abdullah Solihin Mohd Fauzi; Juliza Jamaludin; Wan Zakiah Wan Ismail; Irneza Ismail; Sharma Rao Balakrishnan; Mus’ab Sahrim (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
E-Proceeding Kolokium Siswazah Fakulti Sains Dan Teknologi 2020 (KOSIST 2020) “Synergizing Innovation and Research Through Science and Technology” 9th December 2020 Organized by Faculty Science and Technology